Religião e Estado no Brasil: autonomias específicas e articulações mútuas no período de 2013 a 2023 - Honório, Luiz Henrique Ferfoglia (2024)
The main objective of this research was to understand, analyze and examine how the relationship between Religion and the State seen from the perspective of the dispute in the institutional field collaborated for the development of social, political and religious conservatism in recent Brazil. Even with the validity of the secularity of the State in Brazil, social and religious groups act more directly in the country's decision-making processes in the predominance and defense of their interests, resuming the discussion on the acceptance and compatibility of this relationship, now under the presentation and updating of new contexts and approaches that ended up imposing new challenges on the approximation of these two magnitudes. It is a bibliographic research, of an exploratory nature, including journalistic and academic texts, publications in books and magazines, which sought to select theories that specifically dealt with this relationship, especially those whose discussions were directed to the scope and limits of the performance of these two magnitudes. In practice, what was observed in the analyzed context was the direct transposition, without mediation, of one magnitude over the other, literally disregarding the concept of secularism that prevails in the country. What has been seen in recent years is the attempt of rulers to appropriate religious concepts in order to implement a permanent political project of power. Likewise, the presence of the religious question in various spaces of power was highlighted, with the novelty of the union of the main Christian-based religious expressions in Brazil acting together in projects strongly linked to a (neo)conservatism that has returned with force in recent years, on the one hand, and on the other, the presence and prominent participation of progressive leaders acting to make this relationship valid